Divismo, maturità e politica sessuale negli "Hollywood film" di Anna Magnani (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
In the 1950s Anna Magnani played an important role in the internationalization of European stardom, becoming the first Italian actress to win an Oscar in 1955. She was 46 years old and had reached international success at the age of 37. Related to the aesthetical concerns of Italian Neorealism, and considered a pioneer in modern representation of female psychology and desire, Magnani’s case puts into question the idea that, according to Edgar Morin, grace, beauty and youth are sine qua non conditions to become a star. Between 1955 and 1960 the actress participated in three Hollywood movies along with mentoring figures such as Tennessee Williams and producer Hal B. Wallis: The Rose Tattoo (Daniel Mann, 1955), Wild is the Wind (George Cukor, 1957) and The Fugitive Kind (Sidney Lumet, 1959). Magnani’s Hollywood films suggest a kind of tailor-made melodrama, concerned in documenting her unique performative style while Hollywood experiences a great renewal of dramatic patterns and acting models. These titles also share a common subject: a passionate mature woman in crisis who, attracted to a younger man, experiences a personal rebirth closely linked to the raise of her sexuality and desire. Through the analysis of these films and how they relate to Magnani’s stardom construction in the Italian postwar, this article investigates the role of the actress in the transit of the 1950s to the 1960s. A season of great transformations in world cinema in which Hollywood, apparently interested in documenting Magnani’s uniqueness, has probably ended up discussing some of the greatest taboos in classic movies: aging over women’s bodies, erotism between mature femininity and young masculinity, or the experience of sex and passion according to a female character who remains the subject of its own desire.
Keywords: Anna Magnani; Hollywood; Aging; Stardom; Age difference; Female maturity